If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -1 + 2y = 4 Reorder the terms: -1 + 3y + 2y = 4 Combine like terms: 3y + 2y = 5y -1 + 5y = 4 Solving -1 + 5y = 4 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 5y = 4 + 1 Combine like terms: -1 + 1 = 0 0 + 5y = 4 + 1 5y = 4 + 1 Combine like terms: 4 + 1 = 5 5y = 5 Divide each side by '5'. y = 1 Simplifying y = 1
| 7x^2+6x+11=0 | | 2*x^2+14*x=3*x+6 | | 8-2k=4 | | ln2x=1/2 | | 7x+2y-x+y= | | P(x)=-8x^2+32x-45 | | 9x^2+48X+69= | | b+7=19 | | 18c^4-16c^2/-2c | | 8x^3+2x-10=0 | | y+683=1000 | | 32x=16x+2 | | Ln(2x-5)=4 | | 8*w^2-34*w+21=0 | | 3x-5=-2x+15 | | Un=8n-7 | | 2x+7=11x+2 | | 7(3x-2)+1=2(3x-1) | | 6f+18= | | 16t^2+192t+64=0 | | 8y-1=12y+5 | | -2-13.8x=-8x-(6x+1) | | X(6x+2)=28 | | 7m+3m+4=24 | | 2(3y+9)=180 | | 1/2*20.0*20.0 | | 4a-6=50 | | 4+55x=44x+13 | | 0=16-(x-x*0.02)/1.19 | | 2x+3y=bx-42 | | 3(a+6)-2(a-6)+4=3-4(1-a) | | -77+x=12 |